فيضان وطاعون بغداد 1830-1831 وانعكاساته على الأوضاع الاجتماعية والاقتصادية: فيضان وطاعون بغداد 1830-1831 وانعكاساته على الأوضاع الاجتماعية والاقتصادية - المشهداني, محمد كريم; صالح, كريم محمد (مجلة دراسات في التاريخ والآثار, 2021)
Abstract            The population of Iraq in general and Baghdadis have been subjected to a wave of natural disasters which caused the death of hundreds of people. Baghdad, for instance, has witnessed a number of plagues, but the most severe one was the one in Persian city of Tibriz in July, 1830 which then moved to Kirkuk and many infected people began to appear. After that the plague moved to Suleimanyah and then to Baghdad. The plague coincided with another disaster which is the flood of Baghdad in the same year forming a real human and environmental disaster on most of the Iraqi cities specially the city of Baghdad, leaving behind sociological, economic effects that would last for long time.